P.160 Safety and effectiveness of the assessment and treatment of idiopathic normal pressure hydrocephalus (iNPH) in the Adult Hydrocephalus Clinical Research Network (AHCRN). (June 2022) - Hamilton, MG; Williams, M; Holubkov, R; Nagel, S; Wisoff, J; Zwimpfer, T; Edwards, R; McKhann, G; Moghekar, A; Golomb, J; Katzen, H; Dasher, N; et al.
Abstract : Background: Idiopathic Normal Pressure Hydrocephalus (iNPH) is a disorder of the elderly with progressive worsening of gait and balance, cognition, and urinary control which requires assessment using criteria recommended by International iNPH guidelines. Methods: Adult Hydrocephalus Clinical Research Network (AHCRN) prospective registry data from 5-centers over a 50-month interval included entry criteria; demographics; comorbidities; examination findings using standard AHCRN gait and neuropsychology assessments; shunt procedures, complications of CSF drainage, complications within 30 days of surgery, and 1-year postoperative follow-up. Results: 547 patients were referred for assessment of suspected-iNPH. 123 patients(21.6%) did not meet clinical criteria to proceed with further testing. 424 patients(74.4%;mean age 76.7 ± 6.0 years;males=269) underwent an LP or lumbar drain, and 193(45.6%) underwent insertion of a ventriculoperitoneal shunt. By 8-12 months after shunt surgery, gait velocity was 0.96±0.35m/s (54% faster than pre-CSF-drainage). Mean MoCA scores increased from 21.0 ± 5.0(median=22.0) at baseline to 22.6±5.5(median=24) 12-months post-surgery. Gait and cognitive improvements were clinically significant. No deaths occurred. 8% of shunt-surgery patients experienced minor complications. The 30-day reoperation rate was 4.1%. Conclusions: This AHCRN study demonstrated that CSF-drainage testing of patients with suspected-iNPH successfully identified those who could undergo CSF-shunt surgery with a high rate of improvement and a low rate of complications.